CDKN2A is the main susceptibility gene in Italian pancreatic cancer families. Issue 3 (24th February 2012) - Ghiorzo, Paola; Fornarini, Giuseppe; Sciallero, Stefania; Battistuzzi, Linda; Belli, Fiorenza; Bernard, Loris; Bonelli, Luigina; Borgonovo, Giacomo; Bruno, William; De Cian, Franco; DeCensi, Andrea; Filauro, Marco; et al.
Abstract : Background: Most familial pancreatic cancer (FPC) remains unexplained. The identification of individuals with a high genetic risk of developing pancreatic adenocarcinoma (PC) is important to elucidate its biological basis and is critical to better define emerging strategies for the detection of early pancreatic neoplasms. Patients and methods: A series of 225 consecutively enrolled patients with PC were tested for CDKN2A mutations. After personal and family cancer histories of all the patients had been reviewed, a subset of the patients were classified as FPC and were also tested for mutations in PALLD, PALB2, BRCA1 and BRCA2 as FPC candidate genes. Results: The CDKN2A mutation rate in the 225 PC cases was 5.7%. The CDKN2A founder mutations, p.E27X and p.G101W, were predominant, but the mutation spectrum also included p.L65P, p.G67R and two novel, potentially pathogenic variants, promoter variant c.-201ACTC>CTTT and p.R144C. None of the patients with FPC harboured germline mutations in PALLD, PALB2 or BRCA2 . One family was positive for the BRCA1 UV variant p.P727L. Strikingly, five of 16 patients with FPC (31%) carried CDKN2A mutations. Conclusion: These findings suggest that a sizeable subset of Italian FPC families may carry CDKN2A mutations. This result may be of value for identifying the best candidates for future PC screening trials in Italy.